Early Interleukin-22 and Neutrophil Proteins Are Correlated to Future Lung Damage in Children With Cystic Fibrosis - Renwick, Julie; Reece, Emma; Walsh, Jamie; Walsh, Ross; Persaud, Thara; O'Leary, Cathal; Donnelly, Seamas C.; Greally, Peter (Frontiers in Pediatrics, 2021)
Cystic Fibrosis (CF) lung damage begins early in life. Lung function decline is associated with pulmonary infections, neutrophil infiltration and inflammation. In CF, neutrophils have an altered phenotype. In this pilot study, we aimed to determine if signals of dysfunctional neutrophil responses were evident early in life and whether these signals may be associated with lung damage in later childhood. We examined the pulmonary protein profiles of 14 clinical stable infants and pre-school children with CF employing the aptamer-based affinity platform, SOMAscan®. High resolution computed tomography (HRCT) was performed on all children after age 6 years and Brody score calculated. A Spearman's rank order correlation analysis and Benjamini-Hochberg adjustment was used to correlate protein concentrations in early life to Brody scores in later childhood. Early life concentrations of azurocidin and myeloperoxidase, were positively correlated with Brody score after age 6 (p = 0.0041 and p = 0.0182, respectively). Four other neutrophil associated proteins; Complement C3 (p = 0.0026), X-ray repair CCP 6 (p = 0.0059), C3a anaphylatoxin des Arginine (p = 0.0129) and cytokine receptor common subunit gamma (p = 0.0214) were all negatively correlated with Brody scores. Interestingly, patients with more severe lung damage after age 6 had significantly lower levels of IL-22 in early years of life (p = 0.0243). IL-22 has scarcely been reported to have implications in CF. Identification of early biomarkers that may predict more severe disease progression is particularly important for the future development of early therapeutic interventions in CF disease. We recommend further corroboration of these findings in prospective validation studies.